Queer Theology on Social Media: A Reflection on Queer Pastoral Influencers on Instagram - Müller, Sabrina (International journal of practical theology, 2025)
The field of Queer Theology can be enhanced by qualitative research on queer lived experiences. The present article addresses this through exploratory observations. The authors examine how two queer pastors (amen_aber_sexy and @tovja_behuetet) express queer issues on Instagram, interact with Christian tradition, and engage in Queer Theology. Within the scope of this article, Instagram emerges as a productive space for lived Queer Theology based on Felix Stalder’s principle of referentiality.